Parametric evaluation and three-dimensional modelling for surface topography of grinding wheel. (May 2019) - Liu, Wei; Deng, Zhaohui; Shang, Yuanyuan; Wan, Linlin
Highlights: The basic topographic parameters of grains on the grinding wheel were characterized by the statistical law of normal distribution. Two new indices were defined for the evaluation of the grain protrusion on the grinding wheel. The three-dimensional model for the diamond grinding wheel is established with the randomness distribution of truncated octahedron grains, and optimized by adjusting the two new indices. The model is valid, and can be effectively used for the grinding simulation. Abstract: The surface topography of a grinding wheel is an indispensable prerequisite for the modelling, simulation and optimisation of grinding. In this study, the basic topographic parameters of grains and two new indices are proposed to parametrically evaluate the surface topography of the grinding wheel, and then a three-dimensional model for the surface topography of the grinding wheel is established. The basic topographic parameters are characterised using statistical methods. Based on the concept of the fraction of the grain protrusion area S r that is optically detected, two new indices, the grain protrusion degree β d and the dispersion degree of the grain protrusion area δ s are defined. Although the grain shape is irregular, a truncated octahedron is used to simulate the diamond grain. By continuous adjustment the distribution of the grain protrusion height σ 2 and the coordinate value of the bond surface z b, the surface topography model becomes closer to reality, when the two indices β d and δ s are similar to that of the actual grinding wheel. Finally, the established three-dimensional model is compared with an actual grinding wheel by the total number of grains per unit area ρ gnS and the grain protrusion height h g, and the accuracy of the model is verified. Graphical abstract: Image, graphical abstract